The impact of road traffic on hydrocarbon content in the sediments of the Škocjan wetland - Bajt, Oliver (Annales. Series historia naturalis, 2008)
Traffic is a very important source of hydrocarbons in the marine environment. In the present work the hydrocarbon content (polyaromatic and aliphatic) in the sediments of a coastal wetland, influenced by road traffic, are presented...
Keywords: kemijska analiza; kvaliteta vode; ogljikovodiki; onesnaževanje; sedimenti; Škocjanski zatok